Acurácia de pontos de corte do perímetro da cintura e da razão cintura-altura na detecção de hipertensão arterial sistêmica na população brasileira : análise da Pesquisa Nacional de Saúde, 2013 - Souza, Ana Paula Alves de (2018)
According to the World Health Organization (WHO), cardiovascular diseases (CVDs) are considered the leading cause of death worldwide. It’s estimated that 55.3% of CVD death sin 2012 occurred due to complications resulting from systemic arterial hypertension. It’s assumed that 20 to 30% of the prevalence of hypertension can be explained by overweight, especially by abdominal obesity, because visceral adipose tissue deposition is strongly linked to cardiovascular risk factors. In this context, anthropometric indicators of abdominal obesity, like waist circumference (WC) and waist-to-height ratio (WHtR), have been used to predict cardiovascular risk due to its easy applicability and low cost. Objective: To identify cut-off points for WC and WHtR in the detection of systemic arterial hypertension in the Brazilian adult and elderly population. Methods: This is a cross-sectional study based on data from the National Health Survey (NHS) carried out in 2013, a national household survey conducted by the Ministry of Health in partnership with Brazilian Institute of Geography and Statistics. Data from 57.230 individuals of both genders and age ≥ 20 years were analyzed. Blood pressure measurements were performed by oscillometric method with an automatic device on the left arm. Blood pressure were measured three times within a 2 minutes interval having their mean data recorded. Patients who presented systolic blood pressure ≥ 140 mmHg and/or diastolic blood pressure ≥ 90 mmHg as well as those who reported the use of antihypertensive medication were classified as hypertensive. Waist circumference was measured on the smallest trunk bending, between the costal margin and the iliac crest and waist-to-height ratio was calculated by dividing the waist circumference (cm) by the height (cm). The ROC curve was used to determine the cut-off points, and the area under and their respective 95% confidence interval (95% CI), sensitivity and specificity of the WC and the WHtR in the detection of hypertension according to sex and age group. It was considered that the greater the area under the ROC curve the greater would the discriminatory power of the anthropometric indicator of hypertension. Results: Cut-off points for WC and WHtR have increased according to the age in both genders. For the WC, the variation amongst men was between 88 and 95.9 cm and amongst women between 85 and 93.2 cm. For the WHtR, cutoff ranged from 0.51 to 0.58 for men and from 0.53 to 0.61 for women. The overall prevalence of hypertension was 32.3% (95% CI = 31.6; 33.0), ranging from 5.8% (95% CI = 4.9; 6.7) to 68.4% (95% CI = 66.4; 70.3) among women and 13% (95% CI = 11.5; 14.7) and 65.6% (95% CI = 63.2; 68.0) among men. Conclusion: Statistical significance was observed in the association among these cutoff points and the presence of hypertension, both for the WC as well as for the WHtR in both genders and in all age groups, with similar performance amongst indicators.